Injury epidemiology in competitive diving athletes: a four-year observational study - Currie, B. M.; Hetherington, M.; Waddington, G.; Brown, N. A. T.; Drew, M. K.; Witchalls, J.; Toohey, L. A. (Journal of Science and Medicine in Sport, 2024)
Objectives To describe the incidence, severity, burden and sport specific characteristics of injuries reported in elite diving athletes.